Refuge, evacuation, exile, return. Spain and the “refugee issue” in Inter-war Europe - Rodrigo, Javier; Alegre Lorenz, David (Hispania Nova, 2022)
This article uses the tools of comparative history to address an important aspect of the Spanish Civil War: the fact that it generated waves of both internally displaced persons and cross-border refugees. Situating the conflict within the context of inter-war Europe, and particularly historical processes of deportation, forced migration, and exile, it analyses the challenges that the crisis of the war and subsequent post-war period in Spain introduced in the realm of humanitarian protection for displaced populations, and how existing international policies largely failed to protect those displaced by the conflict.
Keywords: displacement; refugees; exiles; Spanish Civil War/postwar; Europe XXth century